Preparing the foundations for video-based practice-placement support: establishing the role from a students’ perspective - Taylor , Teri (Research in Learning Technology, 2012)
Currently, many placement-based health programme students within the UK are supported through face-to-face visits from university staff. Whilst cited in literature as being of value, the face-to-face nature of this contact is not supported. Alternatives including video-based communications methods offer the potential for cost effective, environmentally responsible support. However, in order to establish the fitness for purpose of alternative approaches, the content and purpose of current support needs to be understood. This project aimed to investigate student perceptions of the ideal content and purpose of clinical support visits, and alternatives to the current face-to-face approach. Fifty-six Physiotherapy undergraduate students responded to questionnaires with a further nine participating in a follow-up focus group. Participants emphasised the value of the visit in guiding learning, ensuring progression and resolving arising issues, and highlighted concerns over alternative approaches. Focus group participants discussed the importance of personal and professional confidence in directing requirements for support, and went on to propose a menu of options for methods of communication.Whilst limited in some applications, video technologies may be one of the options. Overall, however, this project supports the need for consideration of individualised learning journeys within curriculum planning.Keywords: addressing institutional problem; saving money; problem solving(Published: 30 August 2012)http://dx.doi.org/10.3402/rlt.v20i0.19193